Developing SDG 13 Based Instruments for Critical Thinking and Sustainability Consciousness on Climate Change: A Rasch Model Approach - Najwa Syafaatul Fadhilah; Widi Purwianingsih; Amprasto Amprasto (Siber Nusantara Publisher, 2026)
Abstract: The escalation of the global climate crisis emphasizes the urgency of strengthening Sustainability Consciousness (SC), Critical Thinking Dispositions (CTD), and Critical Thinking Skills (CTS) through education, as emphasized in SDG 13.3. However, integrated measurement instruments for all dimensions in the context of climate change are still limited. This study developed three SDG 13-based instruments (SC, CTD, CTS) for climate change material in 10th grade Biology using the Rasch model approach. Content validation was tested by two biology experts, while empirical trials involved 115 students, with 75 respondents analyzed after misfit elimination. Winsteps analysis showed that all three instruments met unidimensionality (raw variance 38.6%-62.5%; unexplained first variance contrast 6.8%-7.4%) with high reliability (cronbach alpha 0.94-0.97). After item elimination based on fit (valid items) and local independence, 20 SC items, 14 CTD items, and 9 CTS items were obtained with an ideal distribution of difficulty. This instrument is valid, reliable, and supports integrated assessment for ESD climate action learning.